2012
DOI: 10.1161/circulationaha.112.102715
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Elective Major Noncardiac Surgery After Coronary Stent Insertion

Abstract: Background-Guidelines recommend that noncardiac surgery be delayed until 30 to 45 days after bare-metal stent implantation and 1 year after drug-eluting stent implantation. Methods and Results-We used linked registry data and population-based administrative health care databases to conduct a cohort study of 8116 patients (Ն40 years of age) who underwent major elective noncardiac surgery in Ontario, Canada between 2003 and 2009, and received coronary stents within 10 years before surgery. Approximately 34% (nϭ2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
84
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(94 citation statements)
references
References 34 publications
5
84
0
5
Order By: Relevance
“…Stents are expected to provide protection against postoperative AMI in noncardiac surgeries [14]; however, patients with AMI + a stent had a high risk of post-TKA AMI within 1 year of its placement. Previous studies to evaluate the risk of postoperative catastrophic events in the patients with a stent have reported variable recommendations about timing for surgery [10,19,24]. The high risk has been attributed to the discontinuation of antiplatelet drugs before the surgery [10,19,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stents are expected to provide protection against postoperative AMI in noncardiac surgeries [14]; however, patients with AMI + a stent had a high risk of post-TKA AMI within 1 year of its placement. Previous studies to evaluate the risk of postoperative catastrophic events in the patients with a stent have reported variable recommendations about timing for surgery [10,19,24]. The high risk has been attributed to the discontinuation of antiplatelet drugs before the surgery [10,19,24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies to evaluate the risk of postoperative catastrophic events in the patients with a stent have reported variable recommendations about timing for surgery [10,19,24]. The high risk has been attributed to the discontinuation of antiplatelet drugs before the surgery [10,19,24]. This high risk also suggests that the timing of the TKA for some patients with AMI + stent did not comply with the timing (after 6 months) recommended by ACC/AHA for patients after percutaneous coronary intervention.…”
Section: Discussionmentioning
confidence: 99%
“…149 However, recent data have suggested that, beyond six months following newer-generation DES implantation-and, for some specific DES devices, beyond three months of DES implantation-the perioperative cardiac event rates may be acceptable. 126,132,150 Independently of the interval between DES implantation and surgery, aspirin should be continued and, in cardiac-stable/asymptomatic patients with recent myocardial infarction treated with stenting, the timing of non-cardiac, non-urgent surgery will in part be dictated by the type of stent implanted.…”
Section: Revascularizationmentioning
confidence: 99%
“…Our group has used these data extensively to perform evaluative analyses. [12][13][14][15] We used the Ontario Health Insurance Plan claims database, which captures information on services provided by practising physicians, to identify physician visits and stress testing. We used the Canadian Institute for Health Information Discharge Abstract Database, which includes information about hospital admissions, to identify inhospital stress testing and additional comorbidities.…”
mentioning
confidence: 99%